2005
DOI: 10.1002/bjs.4839
|View full text |Cite
|
Sign up to set email alerts
|

Gastrectomy with extended lymphadenectomy for primary treatment of gastric cancer

Abstract: Evidence for D2 dissection is inconclusive. No overall survival advantage has emerged, but some patients with intermediate stage disease may benefit. Excess operative mortality appears to be associated with pancreatico-splenectomy, low case volume and lack of specialist training.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
49
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(55 citation statements)
references
References 39 publications
(59 reference statements)
1
49
0
5
Order By: Relevance
“…In fact, the results from these meta-analysis have confirmed that the findings from those trials concerning morbidity and mortality can be formally accepted. The notion that mortality rates have been greatly reduced, based on the results from recent clinical trials on the surgical treatment of gastric cancer and that extended lymph node resection can be performed safely in experienced centers is unlikely to be valid 6,14,16,17,19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, the results from these meta-analysis have confirmed that the findings from those trials concerning morbidity and mortality can be formally accepted. The notion that mortality rates have been greatly reduced, based on the results from recent clinical trials on the surgical treatment of gastric cancer and that extended lymph node resection can be performed safely in experienced centers is unlikely to be valid 6,14,16,17,19 .…”
Section: Discussionmentioning
confidence: 99%
“…These studies involved 1549 patients, of whom 791 were allocated to the D1 surgical procedure, 617 to D2 and 141 to D3. A systematic review was conducted by McCulloch et al 6 , in 2005, including randomized and non-randomized comparisons between D1 and D2 gastrectomy for primary treatment of gastric cancer. The meta-analysis was performed separately; 15 separate studies were selected, comprising two randomized trials, two non-randomized comparisons and 11 cohort studies reporting results from one technique only.…”
Section: Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Lymphadenectomy is considered essential for gastric cancer surgery; however, the extent of lymph node removal is still debated in the literature [1][2][3][4][5][6]. In Asia, extended lymph node dissection has long been the standard of care for patients with advanced gastric cancer [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Пятилетняя выживаемость больных РРЖ после радикаль-ного хирургического лечения варьирует в пределах 85-95%, что значительно превышает таковую при РЖ с глубиной инвазии Т2 и более [5,6]. Благоприятный прогноз обусловлен низкой ча-стотой лимфогенного и гематогенного метастазирования при РРЖ.…”
unclassified